Peter Rabbit's Little Treasury - Potter, Beatrix (Penguin Group, 2000)
This book brings together four of the most famous stories starting with the most beloved and well known of all, The Tale of Peter Rabbit.
Keywords: Animals; Juvenile Fiction; Rabbits